2022
DOI: 10.37934/araset.27.1.4561
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ultrasonic-Assisted Drilling (UAD) Parameters For Hole Making Of Ti-6Al-4V Using Taguchi Method

Abstract: Ti-6Al-4V is widely used in high-tech industries due to its lightweight, high strength and corrosion resistance. Nevertheless, machining Ti-6Al-4V is very challenging given its low thermal conductivity. Ultrasonic Assisted Drilling (UAD) is one of the best machining techniques. In the manufacturing industry, hole-making is the final step before the end product is produced. The selection of parameters is crucial in obtaining accurate hole accuracy and a smooth surface finish. Cutting speed, feed rate, frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…As the kerosene was generated at lower EWR compared to RBD palm oil, it might due to the protective effect of the deposited carbon layer on the copper electrode. Thus, in terms of EWR, it can be concluded that RBD palm oil exhibited a pattern similar to kerosene, despite significant differences at higher peak current [29][30][31][32][33][34]. This proves that palm oil can be used in the EDM machining process.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…As the kerosene was generated at lower EWR compared to RBD palm oil, it might due to the protective effect of the deposited carbon layer on the copper electrode. Thus, in terms of EWR, it can be concluded that RBD palm oil exhibited a pattern similar to kerosene, despite significant differences at higher peak current [29][30][31][32][33][34]. This proves that palm oil can be used in the EDM machining process.…”
Section: Resultsmentioning
confidence: 90%
“…The figures depict the surface morphology based on the lowest and highest EWR when kerosene and RBD palm oil were used as dielectric fluids. As a result, the lower EWR has shown the distribution of the deposited material is wider and more compared to the highest EWR resulted [13,[29][30][31][32][33][34][35]. In contrast to lower EWR, higher EWR indicates a wider shape of material deposited upon that copper electrode surface despite the higher peak current applied, which resulted in more material deposited melting.…”
Section: Resultsmentioning
confidence: 99%
“…Ti6Al4V, a titanium alloy, possesses exceptional mechanical properties, a high strength-to-weight ratio, and excellent corrosion resistance, making it widely used in various industries, including aircraft [6], automotive [7], and medical [8]. However, the native surface of Ti6Al4V material exhibits high wettability, leading to a tendency to attract and retain water droplets.…”
Section: Introductionmentioning
confidence: 99%
“…The problem comes when the temperature of the crude oil falls below the wax appearance temperature, causing crystallization in the crude oil [3]. This results in the in the paraffin molecules in petroleum oil precipitating and depositing on the cool pipe's wall, which affects the pipeline flow assurance problem in the pipeline system [4,5]. The thickness of the paraffinic wax can rapidly increase in the solid phase, clogging the pipeline.…”
Section: Introductionmentioning
confidence: 99%